India and the WTO - Mattoo, Aaditya; Stern, Robert M. (Robert Mitchell), 1927-2015 (World Bank e-Library., 2003)
This book is designed to clarify India's interests in the World Trade Organization's Doha Development Agenda and to provide a blueprint for its strategy in multilateral negotiations. The focus is on facilitating domestic and external policy reforms that can serve to bolster India's participation in the multilateral trading system and to enhance the effectiveness of India's trade and related policies in achieving developmental goals.